ALL THE LIVES HE LED - Pohl, Frederik (New York: A Tom Doherty Associates Book, 2011)
A near-future tale finds a popular theme park opened on the site of ancient Pompeii on the eve of the 2,000th anniversary of the eruption of Vesuvius and threatened by a possible repeat eruption and terrorist attack.